2017
DOI: 10.1016/j.jped.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal screening: 9% of children with filter paper thyroid-stimulating hormone levels between 5 and 10 μIU/mL have congenital hypothyroidism

Abstract: The study showed that 9.13% of the children with b-TSH levels between 5 and 10μIU/mL developed hypothyroidism and that in approximately one-quarter of them, the diagnosis was confirmed only after the third month of life. Based on these findings, the authors suggest the use of a 5μIU/mL cutoff for b-TSH levels and long-term follow-up of infants whose serum TSH has not normalized to rule out congenital hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Of note, several NSPs have established their neoTSH cutoff values based on the recommendation of collecting blood in filter paper between the third and fifth days of life. However, we observed in our country that the sample collection and analysis take a longer time, hindering proper interpretation of the results (18,33). In our results, less than half of the study population was screened within the recommended lifespan, probably due to poor staff training and public transport, which could be a potential limitation.…”
Section: Epidemiological Profile Of Congenital Hypothyroidismmentioning
confidence: 60%
See 1 more Smart Citation
“…Of note, several NSPs have established their neoTSH cutoff values based on the recommendation of collecting blood in filter paper between the third and fifth days of life. However, we observed in our country that the sample collection and analysis take a longer time, hindering proper interpretation of the results (18,33). In our results, less than half of the study population was screened within the recommended lifespan, probably due to poor staff training and public transport, which could be a potential limitation.…”
Section: Epidemiological Profile Of Congenital Hypothyroidismmentioning
confidence: 60%
“…Table 4 shows the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of different cutoff values for neoTSH in the study cohort. The NSP of Campinas University (Unicamp) reported a prevalence of CH of 9.13% based on neoTSH values ranging between 5-10 mIU/L (18). In Sergipe, the total incidence of CH was 1:3,461 (19), and in the state of Mato Grosso, the incidence was 1:2,234 screened newborns (15), using neoTSH cutoff values of 5.2 and 5.0 mIU/L, respectively.…”
Section: Epidemiological Profile Of Congenital Hypothyroidismmentioning
confidence: 99%
“…However, this percentage is very likely overestimated given that that the number of days from birth to blood collection has a great influence. These data are important, as it should be borne in mind that a high percentage of the 9% of newborns with TSH values between 5–10 mIU/L may eventually present congenital hypothyroidism and it is, therefore, important to establish a cut-off point and a fixed day of age at sampling, or changing values according to days from birth to sample collection [2729].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Kilberg et al suggested that US neonatal screening programs were missing newborns with mild and persistent TSH elevations, who could have CH and its health consequences, due to the lack of adequate standardization of TSH values [15]. Christensen-Adad PLOS ONE et al (2017) also demonstrated that 9% of children with TSH values between and 5-10 μIU/ mL (screening test cut-off = 10 μIU/mL), who did not normalize these values over time, had CH that would not have been diagnosed by the national recommended cut-off value [16].…”
Section: Introductionmentioning
confidence: 99%